Psychomotor activities with seniors - Jitka Kopřivová; Roman Grmela (Palacký University Olomouc, 2015)
BACKGROUND: Given that the population all over the world is aging, it is necessary to fi nd ways to help maintain or improve the quality of life of seniors. The main goal of this paper is to show how appropriate physical activity programs contribute to the improvement of the functionality and psychosocial wellbeing of seniors. We are particularly interested in the possibilities of preserving self-suffi ciency and self-service, independence and the ability to perform everyday activities. One of the most eff ective forms of physical activity is psychomotr activity. OBJECTIVE: The aim of our paper is to present basic information concerning the meaning and the application of the psychomotr activities in intervention movement programmes in order to improve seniors’ life quality. METHODS: We defi ne the term psychomotr activities according to Adamírová (1995) and Novotná (2010). In this paper we present some results of research that stress the positive eff ect of psychomotor exercises and games on the life satisfaction of the elderly (Stará 2011; Stará & Kopřivová, 2011). DESCRIPTION: According to the results of our research and practical experience gained from working with the elderly it is strongly recommended to include suitable psychomotor exercises and games focusing on the development of manual dexterity in training programs in order to improve the balance abilities and the psychosocial area. In terms of prevention, because of the growing number of neurological disorders at an old age it is appropriate to include psychomotor exercises that encourage the development of cognitive functions in the physical interventions. CONCLUSION: We were able to positively infl uence the emotional aspect from performing physical activities, to enhance self-esteem of the exercising subjects and to create new social relationships. Motion programs, which also included psychomotor exercises and games, had a positive eff ect on the physical assessment of the seniors and on all the attributes of health.